Commercial factors that determine the exportable offer of Chenopodium quinoa from Peru - Linares Vizcarra, Mitzi Lourdes Del Carmen (2020)
Through this research work, we reflect the commercial factors that determine the exportable supply of Chenopodium quinoa, which from now on we will call by its commercial name “Quinoa” or “Quinoa” from Peru. The problem focuses on the competition levels between current producing economies and the latent evolution of importing economies into future suppliers, which are becoming increasingly competitive due to the factors that we will develop in this article. That being said, we need to be careful how we will present the product, which determines the exportable offer of quinoa. The Objectives: Describe the commercial factors and prove their germaneness in the construction of the exportable offer, and how, the final product quality influences on the export of Peruvian quinoa. Methodology: It will be carried out through a data analysis process, which will be previously collected, so a deductive approach will be used. Results: The statistical analysis performed for this study was developed first in MS Excel to perform market segmentation and obtain the degree of prioritization, and then in SPSS, the Two-step cluster analysis was performed; likewise, analyzed data was used to prepare statistical tables and graphs in order to interpret the results. Research Conclusions: The Ministries of Foreign Trade and Agriculture must consider the commercial variables to strengthen the quinoa production chain in a sustainable and profitable way.